The Use of Neuroimaging for Predicting Sumatriptan Treatment Response in Patients With Migraine - Wu, Jr-Wei; Lai, Pi-Yi; Chen, Yung-Lin; Wang, Yen-Feng; Lirng, Jiing-Feng; Chen, Shu-Ting; Lai, Kuan-Lin; Chen, Wei-Ta; Wu, Yu-Te; Wang, Shuu-Jiun (Frontiers in Neurology, 2022)
Objectives To identify the neuroimaging predictors for the responsiveness of patients to sumatriptan and use an independent cohort for external validation. Methods Structuralized headache questionnaire and 3-Tesla brain magnetic resonance imaging were performed in migraine patients. Regional brain volumes were automatically calculated using FreeSurfer version 6.0, including bilateral amygdala, anterior cingulated cortex, caudate, putamen, precuneus, orbitofrontal cortex, superior frontal gyri, middle frontal gyri, hippocampus, and parahippocampus. A sumatriptan-responder was defined as headache relief within 2 h after the intake of sumatriptan in at least two out of three treated attacks. We constructed a prediction model for sumatriptan response using the regional brain volume and validated it with an independent cohort of migraine patients. Results A total of 105 migraine patients were recruited, including 73 sumatriptan responders (69.5%) and 32 (30.5%) non-responders. We divided the migraine patients into derivation (n = 73) and validation cohorts (n = 32). In the derivation cohort, left hippocampal volume was larger in sumatriptan responders (responders vs. non-responders: 3,929.5 ± 403.1 vs. 3,611.0 ± 389.9 mm3, p = 0.002), and patients with a larger left hippocampal volume had a higher response rate to sumatriptan (>4,036.2 vs. ≤4,036.2 mm3: 92.0 vs. 56.3%, p = 0.001). Based on the findings, we constructed a prediction model using the cutoff value of 4,036.2 mm3, and we found that patients with a left hippocampal volume >4,032.6 mm3 had a higher response rate to sumatriptan than those with a left hippocampal volume ≤4,032.6 mm3 (84.6 vs. 42.1%, odds ratio [OR] = 7.6 [95% confidence interval = 1.3–44.0], p = 0.013) in the validation cohort. Conclusion Our study showed that left hippocampal volume is helpful to identify sumatriptan non-responders. This proof-of-concept study shows that left hippocampal volume could be used to predict the treatment response to sumatriptan in migraine patients.